2012
DOI: 10.1016/j.addr.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor delivery: How surface interactions modulate release in vitro and in vivo

Abstract: Biomaterial scaffolds have been extensively used to deliver growth factors to induce new bone formation. The pharmacokinetics of growth factor delivery has been a critical regulator of their clinical success. This review will focus on the surface interactions that control the non-covalent incorporation of growth factors into scaffolds and the mechanisms that control growth factor release from clinically relevant biomaterials. We will focus on the delivery of recombinant human bone morphogenetic protein-2 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 205 publications
(297 reference statements)
3
134
1
Order By: Relevance
“…Wang et al demonstrated minimal loss of unstable proteins during lyophilization 34) . In tissue engineering, there are many ways to control the release of factors, for example use of nanoparticles, hydrogels, or porous scaffolds 35) . Jun et al effectively achieved controlled release of growth factors using tissue engineering scaffolds created by lyophilization 36) .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al demonstrated minimal loss of unstable proteins during lyophilization 34) . In tissue engineering, there are many ways to control the release of factors, for example use of nanoparticles, hydrogels, or porous scaffolds 35) . Jun et al effectively achieved controlled release of growth factors using tissue engineering scaffolds created by lyophilization 36) .…”
Section: Discussionmentioning
confidence: 99%
“…This response is in line with the classic burst release of BMP-2 associated with the clinical use of INFUSE. 23 This effect likely renders ACS unable to ensure longerterm growth factor delivery and has been postulated to contribute to the adverse effects associated with the use of rhBMP-2/ACS clinically. [24][25][26] Relative to all other scaffolds, the S(P) gel showed a superior rate of initial growth factor binding, followed by a steady and sustainable release over the period studied.…”
Section: Figmentioning
confidence: 99%
“…Collagen sponges represent the earliest and best studied materials used for BMP-2 delivery. A disadvantage of this material relies on so-called early burst effects which are often observed upon administration [80]. In order to obtain a sustained release of the protein and decreasing this initial burst release phenomenon, genipin-crosslinked gelatin microparticles have been designed.…”
Section: Non-covalent Binding Strategiesmentioning
confidence: 99%